Animales de día y de noche = Animals day and night - Kenah, Katharine (Columbus, OH : Waterbird Books, 2005)
Presents facts about nocturnal animals, including the koala, hippopotamus, opossum, rhinoceros, skunk, and sun bear.
Keywords: Nocturnal animals -- Juvenile literature; Spanish language materials -- Bilingual